2010
DOI: 10.1021/jf101827v
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal Activity of Cineole Derivatives

Abstract: Essential oils and their constituents have potential as ecologically acceptable pesticides that may also have novel modes of action. In this work hydroxy and ester derivatives of the naturally occurring monoterpenoids 1,8-cineole 3, the main component in most eucalyptus oils, and 1,4-cineole 4 were prepared and their pre-emergence herbicidal activity against annual ryegrass (Lolium rigidum) and radish (Raphanus sativus var. Long Scarlet) investigated in laboratory-based bioassays. 1,8-Cineole, eucalyptus oil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 23 publications
1
54
1
Order By: Relevance
“…Long Scarlet in laboratory-based bioassays. 1,8-cineole and its derivatives showed a dose-dependent herbicidal activity against both weed species [64]. Laboratory studies [64,65] also have shown that soil-applied 1,8-cineole suppressed the growth of several weeds.…”
Section: Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long Scarlet in laboratory-based bioassays. 1,8-cineole and its derivatives showed a dose-dependent herbicidal activity against both weed species [64]. Laboratory studies [64,65] also have shown that soil-applied 1,8-cineole suppressed the growth of several weeds.…”
Section: Essential Oilsmentioning
confidence: 99%
“…1,8-cineole and its derivatives showed a dose-dependent herbicidal activity against both weed species [64]. Laboratory studies [64,65] also have shown that soil-applied 1,8-cineole suppressed the growth of several weeds. However, field reports demonstrated that 1,8-cineole alone has poor herbicidal activity [67,68].…”
Section: Essential Oilsmentioning
confidence: 99%
“…They could be characterized by high biological activity, novel target sites and alternative MOA, low or no toxicity, high biodegradability compared to the commercial herbicides, and consequently an increased environmental and health safety . Until now, natural products have not played an important role in herbicide development compared to other pesticides, although some natural‐like compounds with herbicidal activity have been developed …”
Section: Introductionmentioning
confidence: 99%
“…7 Until now, natural products have not played an important role in herbicide development compared to other pesticides, 8,9 although some natural-like compounds with herbicidal activity have been developed. [10][11][12][13][14][15][16][17][18] In this paper, benzofuran-2-acetic esters are presented as a new class of 'bio-inspired' potential herbicides. 19 The benzofuran motif constitutes the core of many pharmacologically active substances, with biological activities that include anti-inflammatory, anticancer, cytotoxic, antimicrobial, antioxidant, insecticidal and antiplasmodial effects.…”
Section: Introductionmentioning
confidence: 99%
“…DPPH (1,1-diphenyl-2-picrylhydrazyl) radical-scavenging activity was measured according to Barton. [18] Scavenging efficacy was calculated as a percent of decolorization based on the corrected absorbances read at 515 nm. The standard Trolox equivalent antioxidant capacity at zero sample concentration (TEAC 0 ) was obtained by extrapolation to zero sample concentration by linear regression.…”
Section: Analysis Of Quality Parameters Of Bmmentioning
confidence: 99%